Changes and Conflicts in policy speeches on University Teaching - Malagón Plata, Luis Alberto (Education Policy Analysis Archives, 2005)
This article considers multiple perspectives and notions about education that prevailed in the development of universities in Latin America. As complex institutions, universities have been developed following multiple models and through contradictory processes, maintaining ancient traditions and incorporating modern characteristics, to the extent that in contemporary universities it is possible to see the traces of previous models (medieval and modern universities). Accordingly, during the last century, the Latin American model of the university has been marked by conflict, but contrary to other analysis which see weaknesses in conflicts, this article concludes that the conflictive character of universities in Latin America has permitted the development of institutions where complex and critical thought emerged.